2017
DOI: 10.1515/pac-2016-1125
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnesium ions on triphosphate hydrolysis

Abstract: Abstract:The role of metal ions in catalyzing phosphate ester hydrolysis has been the subject of much debate, both in terms of whether they change the transition state structure or mechanistic pathway. Understanding the impact of metal ions on these biologically critical reactions is central to improving our understanding of the role of metal ions in the numerous enzymes that facilitate them. In the present study, we have performed density functional theory studies of the mechanisms of methyl triphosphate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 60 publications
7
44
0
1
Order By: Relevance
“…18,29,31 Our calculations suggest that for most phosphate monoester dianions, a solvent-assisted pathway dominates, although a substrate-assisted pathway becomes viable only for very poor leaving groups. 20 This is borne out also in our study of the effect of metal ions on phosphate hydrolysis, 25 where the solvent-assisted pathway is consistently energetically preferred, in line with our studies of phosphate monoesters. Finally, in the case of the pyridinio-N-phosphonates, 24 where proton transfer is no longer an issue, we obtain loose symmetrical transition states for the reaction with pyridine, in agreement with prior experimental work.…”
Section: Feature Article Chemcommsupporting
confidence: 82%
See 3 more Smart Citations
“…18,29,31 Our calculations suggest that for most phosphate monoester dianions, a solvent-assisted pathway dominates, although a substrate-assisted pathway becomes viable only for very poor leaving groups. 20 This is borne out also in our study of the effect of metal ions on phosphate hydrolysis, 25 where the solvent-assisted pathway is consistently energetically preferred, in line with our studies of phosphate monoesters. Finally, in the case of the pyridinio-N-phosphonates, 24 where proton transfer is no longer an issue, we obtain loose symmetrical transition states for the reaction with pyridine, in agreement with prior experimental work.…”
Section: Feature Article Chemcommsupporting
confidence: 82%
“…6. Our calculations 63 suggested that the phosphatase activity of this enzyme proceeds through a substrate-assisted mechanism, similar to that suggested for other phosphatases [34][35][36]91,92 (although this data will need revisiting in light of our more recent studies of model systems 20,25,63 ). In contrast, the sulfatase activity of this enzyme appears to utilize the active site histidine, H115, as a general base with which to deprotonate the active site nucleophile.…”
Section: Challenges In Modeling Alkaline (And Related) Phosphatasessupporting
confidence: 76%
See 2 more Smart Citations
“…17,18 This method allows us to extensively sample the dynamics of each of these proteins in aqueous solution, and consistently compare the corresponding activation free energies with a single set of EVB parameters. We demonstrate that, in line with the corresponding reaction in aqueous solution, 19 there is a strong energetic preference for the D10-assisted pathway in the β-PGM active site. This mechanism is also the only mechanism that quantitatively reproduces changes in activity upon mutation of key active site residues.…”
Section: Introductionsupporting
confidence: 73%